Hygienic Analysis of Diseases Observed During Climax Period in Women (Republic of Uzbekistan) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Climax is not a disease, but a completely normal physiological period observed in the life of any woman after the age of 45. At this age, the ovaries in a woman's body, which are responsible not only for bearing children, but also for a woman's appearance, gradually begin to stop functioning. Our research confirms the results of previously published work that women's incidence rates increase as they age.